FACTORS OF PERSONAL MOTIVATION IN ERIC RAMIRO KIRSTEN’S MOVIE SCRIPT MIDNIGHT SUN - Nanda Herliana; Andang Suhendi (JOURNAL OF LANGUAGE, 2021)
This study is conducted to analyze the factors of personal motivation in Midnight Sun movie written by Eric Kirsten. This study applies qualitative descriptive method since the process and the result of the research are accomplished descriptively. Then, the theory proposed by McClelland is used in this study. He mentions two types of factors of personal motivation. The factors include internal and external. This study is focused only on internal factors. It is stated that five factors belong to internal factors of motivation. After having analyzed those factors in the movie, only four factors are found in the analysis. They are need, hope, responsibility, self-esteem and achievement, while, job satisfaction is not found in the movie. The four internal factors happen within the protagonist himself. These factors emerge from the characters’ personal motivation. By the internal factors, the protagonist can make his dream come true. In conclusion, the result of this study shows that to realize dream and to avoid adversity, we must have a motivation to make it happen.